(untitled) (Research, Society and Development, 2025)
Four decades after the first detected case of human immunodeficiency virus (HIV) infection, it remains a global public health problem. From patient zero in 1982 to the present, an estimated 85.6 million people have been infected with HIV and 40.4 million people have died from HIV-related illnesses through acquired immunodeficiency syndrome (AIDS) worldwide. Among the strategies adopted by the Ministry of Health to meet the goals of eradicating HIV/AIDS is pre-exposure prophylaxis, which consists of taking daily ARVs to reduce the risk of contracting HIV and has been available in the SUS since 2017. Therefore, the objective of this article is to understand the state of the art on the subject by identifying in the literature the technical training, practices, and challenges faced by nurses in the Family Health Strategy program for the implementation and strengthening of PrEP decentralization. After a narrative literature review, it was possible to highlight that there are challenges to be faced in the decentralization of PrEP, such as stigma and lack of knowledge among the population. Furthermore, the Family Health Strategy plays a healthy role in HIV/AIDS prevention given the characteristics of the program, which is to be close to users and communities. In addition, nursing within the ESF plays an important role in bringing health services closer to the population so that they can be assisted comprehensively.